2015
DOI: 10.1016/j.crhy.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Precursors and triggering mechanisms of granular avalanches

Abstract: The dynamics of inclined granular packings driven towards their stability limits are studied experimentally using imaging techniques as well as acoustic methods. The formers allow to study grain rearrangements during the tilting. The implementation of both passive and active acoustic methods for probing the granular packings, with capabilities for time resolved measurements, provides information on various elastic properties of the layers along the destabilization process, including the transient precursors. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Preliminary developments of an automatic tilting experimental setup have been designed to introduce original results in characterizing precursors and avalanches of granular piles [4,19,23]. For the present work, this experimental setup has been significantly improved to reduce artifacts, including mechanical vibrations and electrostatic effects between the glass beads, to consider different sizes of the packing container, to synchronize several physical measurements not discussed here, and to perform large range of inclinations positives or negatives (Fig.…”
Section: Experimental Setup and Successive Tilting Cycles Principlementioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary developments of an automatic tilting experimental setup have been designed to introduce original results in characterizing precursors and avalanches of granular piles [4,19,23]. For the present work, this experimental setup has been significantly improved to reduce artifacts, including mechanical vibrations and electrostatic effects between the glass beads, to consider different sizes of the packing container, to synchronize several physical measurements not discussed here, and to perform large range of inclinations positives or negatives (Fig.…”
Section: Experimental Setup and Successive Tilting Cycles Principlementioning
confidence: 99%
“…The quasi-static regime is satisfied if the inclination process allows the non-displacement of the grains except when local shear forces reach a critical value related to the Coulomb's friction law. The destabilization is generally characterized by grain rearrangements at the free surface, based on optical measurements [1][2][3] but many other experimental techniques have also been successfully used (see [4] for a comprehensive presentation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In complement, Amon et al [23] have developed a simple 1D frictional model which can explain these precursor events and their quasi-periodicities. So all these processes of pile stability are controlled by several physical factors, including the size of the system (height [24], length [25] width [26][27][28][29]), the density or volume compaction of the packing [16,24,25,30,31] and the tilting regime [32][33][34].…”
Section: A Context Of Dry Avalanchesmentioning
confidence: 99%
“…More recently, Kiesgen de Richter [10] and Kiesgen de 49 Richter et al [11] and Duranteau et al [9] and Delannay 50 et al [12] have confirmed these observations by using two 51 successive improved automatic tilting setups to study partic-52 ular physical parameters that control the dynamic of grain 53 avalanches. Indeed, the size of the system (height [5], length 2 54 [6], width [13][14][15][16]), the density or volume compaction of 55 the packing [5,6,[17][18][19], and the tilting regime [12,20,21] are 56 some parameters that have been studied in previous works. 57 For example, Aguirre et al [18] put in evidence the influence 58 of the packing height h, which is related to an equivalent 59 number n l of bead layers in the container (see Eq.…”
mentioning
confidence: 92%